Modulating Portal Hemodynamics With Vascular Ring Allows Efficient Regeneration After Partial Hepatectomy in a Porcine Model. Issue 1 (July 2018) - Bucur, Petru O.; Bekheit, Mohamed; Audebert, Chloe; Othman, Amnah; Hammad, Seddik; Sebagh, Mylene; Allard, Marc-Antoine; Decante, Benoît; Friebel, Adrian; Miquelestorena-Standley, Elodie; Drasdo, Dirk; Hengstler, Jan G.; et al.
Abstract : Objective: To investigate safety and efficacy of temporary portal hemodynamics modulation with a novel percutaneously adjustable vascular ring (MID-AVR) onto a porcine model of 75% hepatectomy. Background: Postoperative liver failure is a leading cause of mortality after major hepatectomy. Portal flow modulation is an increasingly accepted concept to prevent postoperative liver failure. Nonetheless, the current strategies have shortcomings. Methods: Resection was performed under hemodynamic monitoring in 17 large, white pigs allocated into 2 groups. Eight pigs had ring around the portal vein for 3 days with the aim of reducing changes in hemodynamics due to hepatectomy. Analysis of hemodynamics, laboratory, and histopathological parameters was performed. Results: Percutaneous inflation, deflation, and removal of the MID-AVR were safe. Two (25%) pigs in the MID-AVR group and 4 (45%) controls died before day 3 ( P  = NS). A moderate increase of portal flow rate per liver mass after resection was associated with better survival ( P = 0.017). The portocaval pressure gradient was lower after hepatectomy in the MID-AVR group ( P = 0.001). Postoperative serum bilirubin levels were lower in the MID-AVR group ( P = 0.007 at day 5). In the MID-AVR group, the Ki67 index was significantly higher on day 3 ( P = 0.043) and the architectural derangement was lower ( P < 0.05). Morphometric quantification of the bile canaliculi revealed a significantly lower number of intersection branches ( P < 0.05) and intersection nodes ( P < 0.001) on day 7 compared with the preoperative specimen, in the control group. These differences were not found in the ring group. Conclusions: MID-AVR is safe for portal hemodynamics modulation. It might improve liver regeneration by protecting liver microarchitecture. Abstract : Supplemental Digital Content is available in the text